Chronic kidney disease and risk of mortality, cardiovascular events or end-stage renal disease in older patients with hypertension. (October 2012) - Gentile, Giorgio; Trillini, Matias
Older individuals with a diagnosis of chronic kidney disease are at higher risk of all-cause mortality, cardiovascular (CV) events and end-stage renal disease. In such patients, the glomerular filtration rate may be estimated with different formulas, including the Modification of Diet in Renal Disease and the Chronic Kidney Disease Epidemiology Collaboration equations. The recently published post-hoc analysis of the long-term CV and renal outcomes of the ALLHAT trial that enrolled older patients with hypertension and high CV risk, but very low risk of renal disease progression, clearly highlights the interpretative pitfalls associated with this approach. Until future studies better establish the boundaries of 'normal' glomerular filtration rate in older people, physicians should not underestimate the importance of proteinuria and accurate glomerular filtration rate measurement in choosing the most appropriate antihypertensive combination in daily clinical practice, particularly in patients at high risk of progression to end-stage renal disease.